A Gazing of Blast Domination Number Pro-Jump Graph (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The extensive inquiries of the Blast domination number, this article dissects upsetting the parameter over Jumpgraph. The theoretical properties of the Blast domination number of a jump graph plus its accurate values for some customarygraphs are derived. Relations between the Blast domination number of a jump graph and the Blast domination number of theanalogous graphs are additionally perceived